Ultrahigh-strength high-temperature alpha + beta titanium alloy and preparation method thereof
The elemental ratio of α+β titanium alloy is optimized through the cluster component design method, high content of Zr and appropriate amount of Si are increased, and specific tissue morphology is formed, which solves the shortcomings of existing titanium alloys in room temperature strength and high temperature service temperature, and achieves both ultra-high strength and high temperature performance.
Patent Information
- Application Number
- CN202510027073.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The existing α+β titanium alloys have shortcomings in room temperature strength and high-temperature service temperature, and it is difficult to achieve ultra-high room temperature and service temperatures above 600℃ at the same time.
Through precise alloy design, clustered component design methods are introduced, element ratio is optimized, high content of Zr and appropriate amount of Si is increased, and specific tissue morphology is formed, including primary α phase and transformed β phase and circular or elliptical silicide precipitation.
The room temperature and high temperature performance of ultra-high strength are achieved, which are specifically manifested as the room temperature tensile strength exceeds 1360MPa and the tensile strength of 600℃ exceeds 580MPa, while maintaining good ductility and thermal stability.
Smart Images

Figure CN119800153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ultra-high-strength and high-temperature α+β titanium alloy and a preparation method thereof, belonging to the technical field of new materials. Background Art
[0002] α+β high temperature titanium alloy materials are usually used in key parts such as compressor discs, blades and impellers. The service environment of the alloy has strict requirements on its mechanical properties. The alloy needs to have excellent room temperature and high temperature strength, good plasticity, and thermal stability of the structure. As early as 1954, the United States successfully developed the first aviation dual-phase high temperature titanium alloy Ti-6Al-4V. The Al element has a significant solid solution strengthening effect. Segregation occurs during the solid solution process, and solid solution strengthening improves the strength of the α phase; the V element, as a β phase stabilizing element, can effectively increase the β phase content of the alloy, thereby improving the comprehensive performance of the titanium alloy, but its operating temperature is generally lower than 350℃. With the continuous expansion of the aerospace industry and the gradual improvement of aircraft performance, the application performance requirements of aeroengines have become more stringent. However, the room temperature tensile strength of the general α+β titanium alloy is difficult to break through 1300MPa, and the tensile strength at 600℃ is less than 600MPa. Therefore, the development of high-strength, high-plastic and higher service temperature dual-phase titanium alloys has become the focus of current development.
[0003] Alloying is the main method to improve the mechanical properties of dual-phase titanium alloys. BT14 (Ti-4Al-3Mo-1V) was developed by adding Mo elements that are resistant to high temperature oxidation and reducing V elements with high diffusion rate at high temperatures. Due to the stronger solid solution strengthening effect, the room temperature and high temperature strength of BT14 alloy is effectively improved by the addition of Mo. The neutral element Zr has solid solubility in both α and β phases. The addition of Zr improves the strength and heat resistance of titanium alloys while having little adverse effect on plasticity. Si is an important element for improving the high temperature performance of titanium alloys. Typical dual-phase titanium alloys TC11 (Ti-6.5Al-3.5Mo-1Zr-0.3Si) and Ti62222S (Ti-6Al-2Sn-2Cr-2Zr-2Mo-0.2Si) contain a small amount of Si, which has a unique effect on improving high temperature strength and creep properties. Si is easy to segregate in the α phase to form Cottrell gas clusters. At the same time, Si atoms interact with dislocations, reducing stacking faults in the structure and increasing the energy barriers of slip and cross slip, thereby improving the high-temperature strength of the alloy. In duplex titanium alloys, Si mainly plays a role in solid solution strengthening.
[0004] Chinese invention patent CN109763026A proposes a method for preparing a high-strength Ti-Al-Sn-Zr-Mo-Nb-Cr-Fe titanium alloy, but it is not suitable for service at temperatures above 600°C, and its room temperature tensile strength is only about 1100 MPa.
[0005] Chinese invention patent CN117127059A provides a method for preparing a Ti-Al-Sn-Zr-Mo-Si-Nb-Ta-WBCY series cast high-temperature titanium alloy, with a tensile strength of 600 MPa at 600°C and a room temperature tensile strength of about 1100 MPa. However, the improvement in its strength depends on the addition of rare earth elements in the composition system.
[0006] Chinese invention patent CN111172425B proposes a method for preparing a high-temperature titanium alloy with excellent high-temperature and room-temperature properties. It can be used at temperatures above 600°C, but it has undergone complex hot rolling forming treatment and annealing between passes, and the process is cumbersome.
[0007] Chinese invention patent CN107058801A proposes a high-temperature titanium alloy, whose service temperature is 560°C to 650°C, but after static pressing and heat treatment, its room temperature elongation is less than 6%.
[0008] In general, it is difficult for current dual-phase titanium alloys to achieve ultra-high strength levels at room temperature and service temperatures exceeding 500°C through solid solution strengthening. In response to the above problems, by introducing the cluster plus connected atom model that describes the near-order solid solution chemistry, the mature industrial dual-phase titanium alloy Ti-6Al-4V was analyzed, and its near-order structural unit and corresponding composition formula were found, which served as the basis for the composition design of ultra-high strength and high-temperature α+β titanium alloys. Summary of the invention
[0009] The purpose of the present invention is to address the technical problems of insufficient room temperature performance and low service temperature of α+β titanium alloy; in order to solve the above technical problems, the present invention provides a new ultra-high strength and high temperature α+β titanium alloy with ultra-high strength at room temperature, good plasticity and high strength at 600°C and a preparation method thereof through precise alloy design.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] An ultra-high strength and high temperature α+β titanium alloy, the ultra-high strength and high temperature α+β titanium alloy comprises Ti, Al, V, Mo, Nb, Zr and Si elements, and the mass percentage (wt.%) of the alloy components is as follows: Al: 6.0-7.0, V: 1.0-2.0, Mo: 1.2-2.0, Nb: 0.5-1.5, Zr: 10.0-12.0, Si: 0.15-0.35, Mn≤0.02, C≤0.02, Ni≤0. 01, Sn≤0.20, Cr≤0.04, O≤0.02, P≤0.01, S≤0.01, N≤0.006, Ti: balance; and the alloy elements satisfy the following synergistic variation relationship: 87.8wt.%≤Ti+0.9Zr≤90.3wt.%, 6.2wt.%≤Al+Si≤7.2wt.%, 3.5wt.%≤Mo+Nb+1.9V≤6.5wt.%, wherein Ti, Al, and Mo are the main elements. The titanium alloy composition is a high content of Zr and an appropriate amount of Si elements, which constitutes the core element difference from the existing dual-phase titanium alloy, and the given synergistic variation relationship of the components can more accurately guide the actual alloy production.
[0012] The ultra-high strength and high temperature α+β titanium alloy has a specific organizational morphology: it is composed of a primary α phase and a transformed β phase, and there are round or elliptical silicide precipitations in the organization. p The phase content is about 60% to 75%, and the diameter of the silicide is 250 to 300 nm; no harmful phase is generated after aging at 550°C, and it has excellent thermal stability.
[0013] The ultra-high strength and high temperature titanium alloy has good room temperature ductility and high temperature performance. The typical properties of the alloy are: room temperature yield strength>1310MPa, room temperature tensile strength>1360MPa, room temperature elongation>6%, tensile strength>1GPa at 500°C, and tensile strength>580MPa at 600°C.
[0014] A method for preparing an ultra-high-strength and high-temperature α+β titanium alloy comprises the following steps:
[0015] Step 1: Weigh the ingredients.
[0016] According to the mass percentage of the alloying elements, a Mettler Toledo precision electronic scale is used to accurately weigh the metal ingredients with a purity of 99.98%.
[0017] Step 2: Ingot preparation.
[0018] The accurately weighed metal ingredients are placed in a non-consumable vacuum arc melting furnace, and added according to the melting points of the elements. The titanium, aluminum and zirconium elements with lower melting points are placed at the bottom, and the molybdenum, niobium, silicon and vanadium elements with higher melting points are placed on top. Subsequently, the air in the furnace chamber is evacuated to a vacuum, and high-purity argon gas is introduced to melt the metal materials. The total number of flipping and melting in the process is 5 to 7 times, and the electromagnetic stirring system is turned on 3 to 5 times during this period.
[0019] Step 3: alloy rolling.
[0020] The alloy ingot is placed in a muffle furnace heated to 890°C to 910°C for 30 to 50 minutes. The alloy ingot after the insulation treatment is subjected to 5 to 10 passes of unidirectional rolling with a total pressing amount of 80% to 90% to prepare an alloy plate.
[0021] Step 4: Alloy heat treatment.
[0022] The rolled alloy plate sample is placed in a muffle furnace. After solution treatment at 820-860°C for 30-60 min, the sample is taken out and air-cooled to room temperature. Subsequently, aging treatment is performed at 540-560°C for 3-5 h, the sample is taken out and air-cooled to room temperature to obtain the final product.
[0023] Step 5: Alloy performance and structure testing.
[0024] The microstructure of the alloy was detected by scanning electron microscopy (SEM), and the tensile mechanical properties of the alloy samples were tested at room temperature, 500℃ and 600℃ using a UTM5504 electronic universal tensile testing machine.
[0025] The present invention realizes the concept of the above technical solution as follows:
[0026] 1) Using the applicant's cluster composition design method to design the composition of a new ultra-high strength and high temperature α+β titanium alloy. This method forms cluster structural units based on the interaction between elements, which are [clusters] (connected atoms) x , that is, it is composed of a cluster and x connecting atoms, where the cluster is a coordination polyhedron formed by any solute atom as the center and the matrix atoms in the nearest neighbor shell around it, and the connecting atoms in the next nearest neighbor shell are used to match the average density of the alloy. The cluster composition formula of the typical dual-phase titanium alloy Ti-6Al-4V can be expressed as: α-{[Al-Ti 12 ](AlTi2)} 12 +β-{[Al-Ti 14 ](Ti1Mo2)}5, which provides a basis for understanding the existing α+β titanium alloys and designing high-performance dual-phase titanium alloy compositions.
[0027] 2) According to the applicant's previous work, in the titanium alloy system, according to the element effect and the mixing enthalpy between the element and the matrix element, the elements can be divided into Ti-like elements (including Ti and Zr), Al-like elements (including Al, Sn, Si), and Mo-like elements (including Mo, Nb, and V). In the following, to simplify the expression, the three elements entering the cluster formula are replaced by _T__i_, _A__l_, and __M__o_. Among them, the mixing enthalpy of _A__l_ elements with the matrix elements is relatively negative, the interaction is strong, and they preferentially occupy the central atomic position; the _T__i_ elements will preferentially occupy the cluster position; the __M__o_ elements with relatively positive mixing enthalpy and weak interaction with the matrix elements occupy the connecting atomic position. In order to maintain the same good processing properties and dual-phase characteristics as the Ti-6Al-4V alloy, the new ultra-high strength and high temperature dual-phase titanium alloy keeps the same number of {α} and {β} in the Ti-6Al-4V cluster formula. In order to improve the high temperature strength of the alloy, the main alloying elements are Mo, Nb, and Si. Mo and Nb are used to partially replace V in the Ti-6Al-4V cluster formula, because Mo and Nb elements have lower diffusion rates than V and have better high temperature stability. In addition, the Nb element helps the alloy to form a continuous Al2O3 oxide film, which can improve the oxidation resistance of the alloy. Si is used to partially replace Al in the {α} cluster formula in Ti-6Al-4V. Si addition can effectively improve the high temperature tensile strength and creep strength of titanium alloys. This is achieved to a certain extent through solid solution strengthening and precipitation strengthening of silicides, but when the Si content exceeds 1.5wt.%, coarse silicides are easily formed, resulting in reduced plasticity of the alloy.
[0028] 3) To improve the room temperature strength of the alloy, the main alloying element is Zr, which is used to partially replace Ti in the Ti-6Al-4V cluster formula. Zr and Ti belong to the same transition group. They have similar chemical properties and infinite solid solubility. The addition of Zr causes lattice distortion and produces a solid solution strengthening effect. In addition, more importantly, the Zr content exceeding 6wt.% can provide uneven nucleation particles for silicides and promote the precipitation of silicides in α; the precipitation of silicides can effectively improve the room temperature strength of the alloy, and the synergistic addition of high content of Zr and Si can promote the start of the α phase cone slip system, which makes the alloy have good ductility while maintaining high strength.
[0029] 4) By changing the ratio of Ti, Al, Zr, V, Nb, Mo and Si in the cluster formula, the best multi-element alloying effect is produced. Finally, it was determined that the mass percentages of the main components of the new ultra-high strength and high temperature α+β titanium alloy are Al: 6.0~7.0, V: 1.0~2.0, Mo: 1.2~2.0, Nb: 0.5~1.5, Zr: 10.0~12.0, Si: 0.15~0.35, Mn≤0.02, C≤0.02, Ni≤0.01, Sn≤0.20, Cr≤0.04, O≤0.02, P≤0.01, S≤0.01, N≤0.006, Ti: balance; and the alloy elements satisfy the following synergistic variation relationship: 87.8wt.%≤Ti+0.9Zr≤90.3wt.%, 6.2wt.%≤Al+Si≤7.2wt.%, 3.5wt.%≤Mo+Nb+1.9V≤6.5wt.%, among which Ti, Al and Mo are the main elements.
[0030] Compared with the high-strength α+β titanium alloy suitable for 500°C proposed in the invention of CN117418140A, the composition and mass percentage (wt.%) are Al: 6.2~7.2, V: 1.5~2.5, Mo: 1.5~2.5, Nb: 0.5~1.5, Zr: 13.5~14.5, and other impurity elements are: Mn≤0.02, C≤0.02, Ni≤0.01, Si≤0.20, Sn≤0.20, Cr≤0.04, O≤0.02, P≤0.01, S≤0.01, N≤0.006, Ti: balance. The new ultra-high-strength and high-temperature α+β titanium alloy described in the present invention is different from the comparative patent in the following three aspects: 1) The types and ranges of alloying elements are different. The Zr element range is completely different from that of the comparative patent, and it contains Si, an important element for improving room temperature and high-temperature performance; 2) The strengthening mechanism is different. The addition of Si and a high content of Zr promotes the precipitation and strengthening of silicides in primary α; 3) The introduction of a composition synergistic change control scheme derived from a cluster model is conducive to accurately guiding actual alloy production.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1) The present invention designs and develops a new type of ultra-high strength high temperature α+β titanium alloy based on the cluster composition formula method developed by the applicant. Adding Mo and Nb elements can improve the high temperature strength of the alloy, and adding a high content of Zr and an appropriate amount of Si can promote the uniform precipitation of silicides in the α matrix, producing a significant precipitation strengthening effect.
[0033] 2) The new ultra-high strength and high temperature α+β titanium alloy has a specific organizational morphology: it is composed of primary α phase and transformed β phase, and there are round or elliptical silicide precipitations in the organization. pThe phase content is about 60% to 75%, and the diameter of the silicide is 250 to 300nm. After aging at 550℃, no harmful phase is generated, and it has excellent thermal stability. And according to the cluster composition design method, the element synergistic change relationship is given, which is conducive to the composition control of actual production;
[0034] 3) The new ultra-high strength and high temperature α+β titanium alloy has a high tensile strength at 600℃ while maintaining the ultra-high strength level at room temperature. The typical performance indicators are: room temperature yield strength>1310MPa, room temperature tensile strength>1360MPa, room temperature elongation>6%, tensile strength at 500℃ high temperature>1GPa, tensile strength at 600℃ high temperature>580MPa. It has excellent thermal stability and thermal strength, and can be used as an alternative material for high temperature structural components. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The SEM microstructure of the alloy prepared in Example 1;
[0036] Figure 2 This is the SEM microstructure of the alloy prepared in Example 2;
[0037] Figure 3 This is the SEM microstructure image of the alloy prepared in Example 3. DETAILED DESCRIPTION
[0038] The specific implementation of the present invention is described in detail below in conjunction with the technical solution.
[0039] Embodiment 1:
[0040] This embodiment is an ultra-high strength and high temperature α+β titanium alloy, the mass percentage (wt.%) of each component in the titanium alloy is Al: 6.0wt.%, V: 2.0wt.%, Zr: 12wt.%, Nb: 1.5wt.%, Mo: 1.2wt.%, Si: 0.35wt.%, the remainder is Ti element and other inevitable impurities, corresponding to the lower limit of the main element content and the upper limit of the other element content within the given synergistic variation range. The mass purity of the aluminum, vanadium, zirconium, molybdenum, niobium, silicon and titanium is 99.98%.
[0041] Step 1: Weigh the ingredients.
[0042] According to the mass percentage of the alloying elements, a Mettler Toledo precision electronic scale is used to accurately weigh the metal ingredients with a purity of 99.98%.
[0043] Step 2: Ingot preparation.
[0044] The accurately weighed metal ingredients are placed in a non-consumable vacuum arc melting furnace, and the elements are added according to their melting points. The titanium, aluminum and zirconium elements with lower melting points are placed at the bottom, and the molybdenum, niobium, silicon and vanadium elements with higher melting points are placed on top. Subsequently, the air in the furnace chamber is evacuated to a vacuum, and high-purity argon gas is introduced to melt the metal materials. The total number of flip melting times during the process is 5 times, and the electromagnetic stirring system is turned on 5 times during this period.
[0045] Step 3: alloy rolling.
[0046] The alloy ingot was placed in a muffle furnace heated to 890° C. and kept warm for 50 minutes. The alloy ingot after the heat preservation treatment was subjected to 5 passes of unidirectional rolling with a total reduction amount of 80% to prepare an alloy plate.
[0047] Step 4: Alloy heat treatment.
[0048] The rolled alloy plate sample was placed in a muffle furnace. After solution treatment at 820°C for 60 min, the sample was taken out and air-cooled to room temperature. Subsequently, aging treatment was performed at 540°C for 5 h, the sample was taken out and air-cooled to room temperature to obtain the final product.
[0049] Step 5: Alloy performance and structure testing.
[0050] The alloy microstructure was examined by scanning electron microscopy (SEM). The results showed that the alloy was composed of primary α phase and transformed β phase, and round or elliptical silicides were precipitated in the microstructure. p The average content of the phase is 60%, and the average diameter of the silicide is 275nm, see the attached Figure 1 The room temperature, 500°C and 600°C high temperature tensile mechanical properties of the alloy samples were measured using a UTM5504 electronic universal tensile testing machine: room temperature yield strength YS = 1313MPa, tensile strength UTS = 1361MPa, elongation after fracture EI = 8.6%; high temperature tensile strength UTS = 1045MPa at 500°C, and high temperature tensile strength UTS = 588MPa at 600°C.
[0051] Embodiment 2:
[0052] This embodiment is an ultra-high strength and high temperature α+β titanium alloy, the mass percentage (wt.%) of each component in the titanium alloy is Al: 6.5wt.%, V: 1.5wt.%, Zr: 13wt.%, Nb: 1wt.%, Mo: 1.6wt.%, Si: 0.25wt.%, the remainder is Ti element and other inevitable impurities, corresponding to the median content of each element within a given synergistic variation range. The mass purity of the aluminum, vanadium, zirconium, molybdenum, niobium, silicon and titanium is 99.98%.
[0053] Step 1: Weigh the ingredients.
[0054] According to the mass percentage of the alloying elements, a Mettler Toledo precision electronic scale is used to accurately weigh the metal ingredients with a purity of 99.98%.
[0055] Step 2: Ingot preparation.
[0056] The accurately weighed metal ingredients are placed in a non-consumable vacuum arc melting furnace, and the elements are added according to their melting points. The titanium, aluminum and zirconium elements with lower melting points are placed at the bottom, and the molybdenum, niobium, silicon and vanadium elements with higher melting points are placed on top. Subsequently, the air in the furnace chamber is evacuated to a vacuum, and high-purity argon gas is introduced to melt the metal materials. The total number of flip melting times during the process is 6 times, and the electromagnetic stirring system is turned on 4 times during this period.
[0057] Step 3: alloy rolling.
[0058] The alloy ingot was placed in a muffle furnace heated to 900° C. and kept warm for 40 minutes. The alloy ingot after the heat preservation treatment was subjected to 7 passes of unidirectional rolling with a total reduction amount of 85% to prepare an alloy plate.
[0059] Step 4: Alloy heat treatment.
[0060] The rolled alloy plate sample was placed in a muffle furnace. After solution treatment at 840°C for 45 min, the sample was taken out and air-cooled to room temperature. Subsequently, aging treatment was performed at 550°C for 4 h, the sample was taken out and air-cooled to room temperature to obtain the final product.
[0061] Step 5: Alloy performance and structure testing.
[0062] The alloy microstructure was examined by scanning electron microscopy (SEM). The results showed that the alloy was composed of primary α phase and transformed β phase, and round or elliptical silicides were precipitated in the microstructure. p The average content of the phase is 75%, and the average diameter of the silicide is 300nm, see attached Figure 2 The room temperature, 500℃ and 600℃ high temperature tensile mechanical properties of the alloy samples were measured using a UTM5504 electronic universal tensile testing machine: room temperature yield strength YS = 1334MPa, tensile strength UTS = 1373MPa, elongation after fracture EI = 9.9%; high temperature tensile strength UTS = 1058MPa at 500℃, and high temperature tensile strength UTS = 605MPa at 600℃.
[0063] Embodiment 3:
[0064] This embodiment is an ultra-high strength and high temperature α+β titanium alloy, the mass percentage (wt.%) of each component in the titanium alloy is Al: 7.0wt.%, V: 1.0wt.%, Zr: 10wt.%, Nb: 0.5wt.%, Mo: 2.0wt.%, Si: 0.15wt.%, the remainder is Ti element and other inevitable impurities, corresponding to the upper limit of the main element content and the lower limit of the other element content within the given synergistic variation range. The mass purity of the aluminum, vanadium, zirconium, molybdenum, niobium, silicon and titanium is 99.98%.
[0065] Step 1: Weigh the ingredients.
[0066] According to the mass percentage of the alloying elements, a Mettler Toledo precision electronic scale is used to accurately weigh the metal ingredients with a purity of 99.98%.
[0067] Step 2: Ingot preparation.
[0068] The accurately weighed metal ingredients are placed in a non-consumable vacuum arc melting furnace and added according to the melting points of the elements. The titanium, aluminum and zirconium elements with lower melting points are placed at the bottom, and the molybdenum, niobium, silicon and vanadium elements with higher melting points are placed on top. Subsequently, the air in the furnace chamber is evacuated to a vacuum, and high-purity argon gas is introduced to melt the metal materials. The total number of flip melting times during the process is 7 times, and the electromagnetic stirring system is turned on 3 times during this period.
[0069] Step 3: alloy rolling.
[0070] The alloy ingot was placed in a muffle furnace heated to 910° C. and kept warm for 30 minutes. The alloy ingot after the heat preservation treatment was subjected to 10 passes of unidirectional rolling with a total reduction amount of 90% to prepare an alloy plate.
[0071] Step 4: Alloy heat treatment.
[0072] The rolled alloy plate sample was placed in a muffle furnace. After solution treatment at 860°C for 30 min, the sample was taken out and air-cooled to room temperature. Subsequently, aging treatment was performed at 560°C for 3 h, the sample was taken out and air-cooled to room temperature to obtain the final product.
[0073] Step 5: Alloy performance and structure testing.
[0074] The alloy microstructure was examined by scanning electron microscopy (SEM). The results showed that the alloy was composed of primary α phase and transformed β phase, and round or elliptical silicides were precipitated in the microstructure. p The average content of the phase is 70%, and the average diameter of the silicide is 250nm, see attached Figure 3The room temperature, 500°C and 600°C high temperature tensile mechanical properties of the alloy samples were measured using a UTM5504 electronic universal tensile testing machine: room temperature yield strength YS = 1334MPa, tensile strength UTS = 1370MPa, elongation after fracture EI = 6.0%; high temperature tensile strength UTS = 1027MPa at 500°C, high temperature tensile strength UTS = 596MPa at 600°C.
[0075] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An ultra-high strength and high temperature α+β titanium alloy, characterized in that: The ultra-high strength and high temperature α+β titanium alloy includes Ti, Al, V, Mo, Nb, Zr, Si, Mn, C, Ni, Sn, Cr, O, P, S, and N elements, and the mass percentage wt.% is as follows: Al: 6.0-7.0, V: 1.0-2.0, Mo: 1.2-2.0, Nb: 0.5-1.5, Zr: 10.0-12.0, Si: 0.15-0.35, Mn≤0.02, C≤0.02, Ni≤0.01, Sn≤0.20, Cr≤0.04, O≤0.02, P≤0.01, S≤0.01, N≤0.006, Ti: balance 2. The ultra-high strength and high temperature α+β titanium alloy according to claim 1, characterized in that: The elements in the ultra-high strength and high temperature α+β titanium alloy satisfy the following synergistic variation relationship: 87.8wt.%≤Ti+0.9Zr≤90.3wt.%, 6.2wt.%≤Al+Si≤7.2wt.%, 3.5wt.%≤Mo+Nb+1.9V≤6.5wt.%, wherein Ti, Al and Mo are the main elements.
3. The ultra-high strength and high temperature α+β titanium alloy according to claim 1, characterized in that: The ultra-high-strength and high-temperature α+β titanium alloy has a specific organizational morphology, which is a dual-state organization consisting of a primary α phase and a transformed β phase, and silicides are precipitated in the organization.
4. The ultra-high strength and high temperature α+β titanium alloy according to claim 3, characterized in that: In the ultra-high strength and high temperature α+β titanium alloy, the primary α p The phase content is 60% to 75%, and the diameter of the silicide is 250 to 300 nm.
5. The ultra-high strength and high temperature α+β titanium alloy according to claim 3, characterized in that: The ultra-high-strength and high-temperature α+β titanium alloy has no harmful phase generation after aging at 550°C and has good thermal stability.
6. The ultra-high strength and high temperature α+β titanium alloy according to claim 1, characterized in that: The typical properties of the ultra-high strength and high temperature α+β titanium alloy are: room temperature yield strength>1310MPa, room temperature tensile strength>1360MPa, room temperature elongation>6%, high temperature tensile strength>1GPa at 500°C, and high temperature tensile strength>580MPa at 600°C.
7. A method for preparing the ultra-high strength and high temperature α+β titanium alloy according to any one of claims 1 to 6, characterized in that: The following steps are involved: The first step is to weigh the ingredients, and use metal ingredients with a purity of 99.98% according to the mass percentage of the alloy components; The second step is to prepare the ingot, put the metal ingredients in a non-consumable vacuum arc melting furnace, and add the elements according to their melting points, with titanium, aluminum and zirconium with low melting points placed at the bottom, and molybdenum, niobium, silicon and vanadium with high melting points placed on top; The third step is to evacuate the air in the non-consumable vacuum arc melting furnace, introduce high-purity argon gas, and melt the metal ingredients to obtain an alloy ingot; and place the alloy ingot in a muffle furnace for heat preservation treatment; The fourth step is to perform multiple unidirectional rolling on the alloy ingot after the insulation treatment, with a total pressing amount of 80% to 90%, to prepare an alloy plate; In the fifth step, the rolled alloy plate sample is placed in a muffle furnace, and the sample is taken out after solution treatment and air-cooled to room temperature; then, an aging treatment is performed, and the sample is taken out and air-cooled to room temperature to obtain the final product.
8. The method for preparing an ultra-high strength and high temperature α+β titanium alloy according to claim 7, characterized in that: The melting process of the third step is as follows: the total number of melting turns is 5 to 7 times, during which the electromagnetic stirring system is turned on for 3 to 5 times; the temperature of the heat preservation treatment is 890° C. to 910° C., and the heat preservation time is 30 to 50 minutes.
9. The method for preparing an ultra-high strength and high temperature α+β titanium alloy according to claim 7, characterized in that: In the fourth step, 5 to 10 passes of unidirectional rolling are performed.
10. The method for preparing an ultra-high strength and high temperature α+β titanium alloy according to claim 7, characterized in that: In the fifth step, the temperature of the solution treatment in the muffle furnace is 820-860° C. and the time is 30-60 min; the temperature of the aging treatment is 540-560° C. and the time is 3-5 h.
Citation Information
Patent Citations
Cast titanium alloy applicable to 560 DEG C-650 DEG C
CN107058801A
High-strength casting titanium alloy and preparation method thereof
CN109763026A
A high-silicon high-temperature titanium alloy and its preparation method
CN111172425B
Cast high-temperature titanium alloy used at 600 DEG C and preparation method thereof
CN117127059A
High-strength alpha + beta titanium alloy suitable for 500 DEG C and preparation method of high-strength alpha + beta titanium alloy
CN117418140A